2019
DOI: 10.1007/s10620-019-5474-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Angiotensin II Signaling Blockade on Clinical Outcomes in Patients with Inflammatory Bowel Disease

Abstract: Background: Preclinical data demonstrates that activation of the renin-angiotensin system (RAS) contributes to mucosal inflammation, and RAS inhibition by angiotensin converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB) improves colitis in animal models. Less is known regarding the effects of RAS inhibition on clinical outcomes in inflammatory bowel disease (IBD) patients. Aims: Evaluate the impact of ACEI and ARB on clinical outcomes in IBD. Methods: Rates of IBD-related hospitalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…31 In patients with IBD who are inhibited by angiotensin, hospitalization, surgery, and corticosteroid use are less frequent. 32 In the present study, of the 19 hub genes, ACE2 is the main component of the renin-angiotensin system. We found that expression of ACE2 was higher in the colon than in the ileum of patients with IBD.…”
Section: Discussionmentioning
confidence: 75%
“…31 In patients with IBD who are inhibited by angiotensin, hospitalization, surgery, and corticosteroid use are less frequent. 32 In the present study, of the 19 hub genes, ACE2 is the main component of the renin-angiotensin system. We found that expression of ACE2 was higher in the colon than in the ileum of patients with IBD.…”
Section: Discussionmentioning
confidence: 75%
“…Although our study demonstrated that rates of adverse disease activity outcomes were generally lower in patients with IBD prescribed ACE-I or ARB therapy, the results were less striking than those of previous smaller studies. [1,7] It may be that longer follow-up in this cohort of patients will provide more conclusive evidence that these drugs have a beneficial effect on the natural history of IBD.…”
Section: Correspondencementioning
confidence: 99%
“…In addition, the endothelial junctions of the blood vessels at the site of inflammation are more dilated resulting in a leaky vasculature allowing access of macromolecules to the basolateral surface. Thus, we believe that targeting angiotensin II type 1 receptors (ATR1) located at the basolateral surface by ATR1 blockers (ARBs) would be beneficial in treating IBD by attenuating the angiotensin II‐mediated inhibition of Pgp. Thus, modulation of Pgp (MDR1) by Ang II/ATR1 appears to be a novel potential target for the treatment of gut inflammatory disorders including IBD.…”
Section: Discussionmentioning
confidence: 99%